Defining the Principles of Normative Idiom in Spatial Planning (Prostor, 2025)
The research investigates the adherence to and breaches of the general principles of legal drafting (clarity, precision, simplicity) in urban development plans within the Croatian physical planning system. It defines specific principles derived from these general ones by examining the legal and material foundations of the plans' content and implementation, as well as the desirable characteristics of their textual structure and format.